The Management of Dengue Hemorrhagic Fever Endemicity in Semarang City, 2010–2019 - Najwa Reyka Salsabila; Carolina Santi Muji Utami (Universitas Islam Negeri Sumatera Utara, 2026)
Dengue Hemorrhagic Fever (DHF) is one of the infectious diseases that remains a public health problem in the city of Semarang. From 2010 to 2019, the number of DHF cases fluctuated, with an upward trend during certain periods. This study aims to analyze the dynamics of DHF cases in the period 2010 to 2019, as well as to examine the response of the government and the community in efforts to combat it. This study discusses how DHF cases in Semarang City fluctuate each year and what kind of response is taken to control the disease. The research method used is the historical method, which consists of four elements: heuristics, source criticism, interpretation, and historiography. Data was obtained from newspaper archives, reports, and relevant previous studies. The results of the study show that the fluctuation in dengue fever cases is also influenced by environmental factors, population density, and seasonal changes, while the government and community responses are carried out through mosquito breeding site eradication programs, fogging, and health education. Combating dengue fever requires continuous cooperation between the government and the community so that dengue fever cases can be reduced more effectively.